Positron emission tomography in patients with aggressive fibromatosis/desmoid tumours undergoing therapy with imatinib - Kasper, Bernd; Dimitrakopoulou-Strauss, Antonia; Strauss, Ludwig G.; Hohenberger, Peter (European journal of nuclear medicine and molecular imaging, 2010)
We used 18F-FDG PET to evaluate the FDG uptake in patients with aggressive fibromatosis (AF, also known as desmoid tumours) undergoing therapy with imatinib (imatinib mesylate, Glivec).